2009
DOI: 10.1186/1475-2875-8-139
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial activity of a cis-terpenone

Abstract: Background: Malaria is the third most prevalent cause of infectious disease in the world. Resistance of the parasite to classical drugs makes the discovery of new and effective drugs more urgent. The oxidized derivative of hydroxy-cis terpenone (OHCT) is a synthetic molecule that is not toxic to cultured human liver cells at concentrations as high as 60 μM and inhibits activity of cytochrome P450s that metabolize many drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Relatively low-cost treatment regiments are available against malaria, but the emergence and persistent spread of resistance against all existing therapies have aggravated the disease burden in endemic regions [ 66 , 67 ]. Based on their chemical nature, the currently used antimalarials can be grouped under nine classes (see Figure 2 ): 4-aminoquinolines, 8-aminoquinolines, amino-alcohols, sulfamines and sulfones, Biguanides, diaminopyrimidine, sesquiterpenes lactones, naphthoquinones, and antibiotics [ 68 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Relatively low-cost treatment regiments are available against malaria, but the emergence and persistent spread of resistance against all existing therapies have aggravated the disease burden in endemic regions [ 66 , 67 ]. Based on their chemical nature, the currently used antimalarials can be grouped under nine classes (see Figure 2 ): 4-aminoquinolines, 8-aminoquinolines, amino-alcohols, sulfamines and sulfones, Biguanides, diaminopyrimidine, sesquiterpenes lactones, naphthoquinones, and antibiotics [ 68 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…The result showed that the monoacylated showed high activity and lower toxicity, while the diacylated showed lower activity, thus acylation only at the C-15 hydroxy group may be worthy of further antimalarial investigation. Mayer et al (2009) studied the activity of Oxidized Hydroxyl of Cis Terpenone (OHCT) against chloroquine and artemisinin resistant. The result showed that OHCT was more active than chloroquine on chloroquine resistant but less active against chloroquine sensitive while OHCT and chloroquine exhibited similar potency against chloroquine resistant clone.…”
Section: Anti-malarial Effectmentioning
confidence: 99%
“…The OHCT found even at low nano molar concentration, able to inhibit survival of artemisinin resistant isolates. It is therefore concluded that OHCT has the potential capabilities to be developed as anti-malarial lead compound especially as it is easily synthesized (Mayer et al, 2009).…”
Section: Anti-malarial Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is central to any strategy for effective reduction of mortality related to malaria, since an efficient vaccine is yet to be approved [ 1 ]. The emergence and relentless spread of resistance against all the drugs in current use, including the newly introduced artemisinin-based combination therapy, have aggravated the disease burden in endemic regions [ 2 , 3 ]. Hence, there is an urgent need to discover new efficacious and safe anti-malarial drugs in order to face this situation.…”
Section: Introductionmentioning
confidence: 99%